Canadian Union Growth - Eastman, Byron (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper specifies a model of trade union membership growth in Canada. Because union growth affects and is affected by wage and price inflation, the model incorporates simultaneous equations with these three variables in endogeneous roles.